A topical approach to life-span development - Santrock, John W. (McGraw-Hill Higher Education, 2005)
Reviewers and adopters have praised John Santrock’s A Topical Approach to Life-Span Development text for its themes of research, applications, and contexts, and students have loved it for its pedagogy and accessible writing. Building on these strengths, the third edition features more than 2,100 citations from the 21st century and new "Careers in Life-Span Development" boxes.